Validity and reliability of a flywheel squat test in sport - Beato, M.; Fleming, A.; Coates, A.; Dello lacono, A. (Journal of Sports Sciences, 2021)
The aims of this study were to examine the test-retest reliability and construct validity of the flywheel (FW)-squat test. Twenty male amateur team sports athletes (mean±SD: age 23±3 years) completed one familiarization session and two testing sessions including: FW-squat test with an inertial load of 0.061 kg.m2, standing long jump (SLJ), countermovement jump (CMJ) and 5-m change of direction (COD-5m) tests, and isokinetic strength assessments of the knee extensor and flexor muscles. Test-retest reliability was assessed with intraclass correlation coefficient (ICC) and coefficient of variation (CV) of data collected. Construct validity was determined as the degree of relationships between the FW-squat test outputs and both athletic tests and isokinetic assessments scores computed with Pearson`s correlation coefficients. Excellent relative (ICC=0.94-0.95) and acceptable absolute (CV=5.9%-6.8%) reliability scores were found for both concentric and eccentric power outputs collected during the FW-squat test. The same outputs showed moderate to large positive correlations with concentric and eccentric knee extensor and flexor muscle peak force values (r range: 0.465-0.566) measured during the isokinetic test. The FW-squat test is a valid and reliable test to assess lower limb performance given its correlation with isokinetic test, as well as its excellent relative and acceptable absolute reliability.